Institutional Capacity for Governmental Protocol Policy Implementation: Evidence from a Regional Bureaucracy - Novi Astova Asnah; Dwi Putranto Riau; Susanti (Journal of Educational Management Research, 2026)
This study aims to analyze the institutional capacity of a regional leadership administration bureau in implementing protocol policy and to identify the factors influencing such capacity. A qualitative case study approach was employed. Data were collected through in-depth interviews, observations, and document analysis involving ten informants representing internal administrative staff, related government agencies, local government officials, and regional leaders. Data were analyzed using the Five Core Capabilities framework, encompassing the capabilities to act and commit, deliver functions, build relationships and secure support, adapt and renew, and achieve coherence. The findings indicate that protocol policy implementation has generally supported the effective execution of leadership activities; however, institutional capacity has not yet been fully institutionalized. Key strengths include staff commitment, operational flexibility, collaborative networks, and adaptive responses to dynamic leadership agendas. Nevertheless, institutional weaknesses remain evident in the absence of detailed internal standard operating procedures, limited organizational learning mechanisms, and system coherence that relies heavily on informal communication and individual experience. These findings imply the need to strengthen internal protocol procedures, institutionalize continuous capacity development and documented post-activity evaluations, and establish formal inter-organizational coordination mechanisms to enhance sustainable institutional capacity.